Ambidextrous Blockchain Governance Approach for Advancing SmartCo's Digital Transformation Using COBIT 2019 Traditional and DevOps - Khairiyah, Izzah; Mulyana, Rahmat; Kusumasari, Tien Fabrianti (Universitas Negeri Semarang, 2025)
Purpose: This study aims to design an ambidextrous governance model based on COBIT 2019 Traditional and DevOps Focus Areas, focusing on DSS05 (Managed Security Services), to enhance SmartCo’s security readiness for blockchain adoption. Methods: Adopting the Design Science Research (DSR) and case study methodology, data were gathered through semi-structured interviews with six key stakeholders at SmartCo and triangulated with internal documents until data saturation was achieved. Governance and Management Objectives (GMOs) were prioritized using organizational design factors, the relevance of COBIT 2019 DevOps guidance, national regulations (ICT Minister No.5/2021 and SOE Ministerial No. PER-2/MBU/03/2023), and insights from prior research. Results: The study presents an ambidextrous design of the seven governance components for DSS05, addressing people, process, and technology dimensions. Recommendations include formalizing dedicated security roles, standardizing procedures, issuing new policies, and adopting a Security Information and Event Management (SIEM) system. Implementation is projected to improve the DSS05 process capability from 3.29 to 3.86. Novelty: This research contributes to the IT governance body of knowledge by proposing a practical pre-implementation governance model for blockchain security in technology-focused enterprises. Its originality lies in the application of the ambidextrous COBIT 2019 framework to the DSS05 objective and the use of a comprehensive multi-criteria prioritization method to guide governance of emerging technologies.